2015
DOI: 10.4110/in.2015.15.4.191
|View full text |Cite
|
Sign up to set email alerts
|

Immune-mediated Liver Injury in Hepatitis B Virus Infection

Abstract: Hepatitis B virus (HBV) is responsible for approximately 350 million chronic infections worldwide and is a leading cause of broad-spectrum liver diseases such as hepatitis, cirrhosis and liver cancer. Although it has been well established that adaptive immunity plays a critical role in viral clearance, the pathogenetic mechanisms that cause liver damage during acute and chronic HBV infection remain largely known. This review describes our current knowledge of the immune-mediated pathogenesis of HBV infection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 81 publications
1
33
0
Order By: Relevance
“…Acute liver injury is a kind of abnormal liver function caused by many factors such as virus infection, improper use of drugs, excessive intake of alcohol, ingestion of toxic food, trauma, and radiation damage . Liver injury is the basis of acute liver failure, and severe or persistent liver injury will eventually lead to liver failure.…”
Section: Introductionmentioning
confidence: 99%
“…Acute liver injury is a kind of abnormal liver function caused by many factors such as virus infection, improper use of drugs, excessive intake of alcohol, ingestion of toxic food, trauma, and radiation damage . Liver injury is the basis of acute liver failure, and severe or persistent liver injury will eventually lead to liver failure.…”
Section: Introductionmentioning
confidence: 99%
“…Acute liver injury is a liver function abnormality that results from multiple reasons, such as viral infection, abuse of drugs or alcohol, ingestion of toxic substance and so on [1,2]. Serious or continuous liver injury often gives rise to liver cirrhosis or liver failure and results in death.…”
Section: Introductionmentioning
confidence: 99%
“…Viral infection and liver damage is often exacerbated through cytokine storm and immune dysregulation (39)(40)(41). Having shown that the IFN status of the immune compartment is critical for controlling generalized infections and liver damage, we sought to assess whether abnormal cytokine levels were an additional component in the liver disease observed in IFN-␣␤␥R Ϫ/Ϫ mice.…”
Section: Ifn-␣␤␥rmentioning
confidence: 99%